JM INOVASI PATEN KECAMATAN SUMBERLAWANG SRAGEN - Joko Mursid; Aris Tri Haryanto; Joko Pramono (JI@P, 2022)
The purpose of this research is to describe the innovation of the DistrictIntegrated Administrative Service (DIAS) in Sumberlawang District, SragenRegency. This type of research is a qualitative research with a case studyapproach. Data collection techniques used: in-depth interviews, documentationstudies, and observation. Data validation uses: trustworthiness, transferability,and certainty. The data analysis technique uses an interactive model. The resultsof the study concluded that: (1) DIAS is a service innovation, has characteristicssuch as: as new knowledge, new ways, has new objects, requires new technologysupport, and is a form of new invention in sub-district organizations in providingservices to the community; (2) Obstacles faced by Sumberlawang Sub-district,Sragen Regency in implementing DIAS innovation, among others: lack of skillsand number of sub-district HR personnel to serve the community, lack ofsocialization to the community, budget support that has not been maximized.However, all these shortcomings are still within reasonable limits so that theimplementation of the DIAS program can still be carried out; (3) The solutionstaken to anticipate the obstacles faced by Sumberlawang Sub-district, SragenRegency in implementing DIAS innovation, include: providing training foremployees on the use of DIAS applications, increasing socialization about DIASto the public, proposing additional budgets in the future, and making efficiencythe existing budget for purposes deemed urgent to implement the DIAS programin order to keep it running.Keywords: Innovation, DIAS